2021
DOI: 10.3390/jcm10102189
|View full text |Cite
|
Sign up to set email alerts
|

Needling Interventions for Sciatica: Choosing Methods Based on Neuropathic Pain Mechanisms—A Scoping Review

Abstract: Sciatica is a condition often accompanied by neuropathic pain (NP). Acupuncture and dry needling are common treatments for pain, and the current literature supports acupuncture as an effective treatment for sciatica. However, it is unknown if the mechanisms of NP are considered in the delivery of needling interventions for sciatica. Our objective was to assess the efficacy and the effectiveness of needling therapies, to identify common needling practices and to investigate if NP mechanisms are considered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…SD rat adolescent bone marrow MSCs were collected and grown as previously described (Chen et al, 2017 ). On the second day following injury, animals in groups A and B underwent electroacupuncture by stimulating Huantiao (GB30) and Zusanli (ST36; Perreault et al, 2021 ; Yu et al, 2022 ). In addition, at the time of modeling, animals in groups A and C received subepidermal microinjections of 5 × 10 5 BMSCs suspended in phosphate-buffered saline (PBS) with a final volume of 3.0 μl.…”
Section: Methodsmentioning
confidence: 99%
“…SD rat adolescent bone marrow MSCs were collected and grown as previously described (Chen et al, 2017 ). On the second day following injury, animals in groups A and B underwent electroacupuncture by stimulating Huantiao (GB30) and Zusanli (ST36; Perreault et al, 2021 ; Yu et al, 2022 ). In addition, at the time of modeling, animals in groups A and C received subepidermal microinjections of 5 × 10 5 BMSCs suspended in phosphate-buffered saline (PBS) with a final volume of 3.0 μl.…”
Section: Methodsmentioning
confidence: 99%
“…A previous clinical trial found that manual therapy, when applied using current knowledge on altered pain processing, gets better short-term and similar long-term effects at 1 year (Fernández-de-las Peñas et al, 2015) and 4 years (Fernández-de-las-Peñas et al, 2020) on pain and function as compared with surgery in women with CTS. The results observed in our trial when applying PENS were like those previously observed with manual therapy at 1-year follow-up (Fernández-de-las Peñas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of altered nociceptive processing may explain the heterogeneity in the clinical outcomes observed in clinical trials. For example, Perreault et al (2021) found that pain mechanisms are not routinely considered in trials investigating needling approaches for neuropathic pain conditions. Accordingly, the aim of this randomized clinical trial was to investigate if the application of PENS targeting the median nerve is effective for improving pain and function in women with CTS as compared to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Used often to treat myofascial pain and trigger/tender points, dry needling can be extremely painful for the patient (29), some might even call it abusive. In dry needling for myofascial trigger-points, a needle is often inserted forcefully and repeatedly deep into the trigger/tender point during a session (e.g., fast-in and fast-out/pistoning/sparrow pecking maneuver, possibly in a fan or cone shape), with the purpose of "destroying" the trigger point or trying to induce edema, positive inflammation, and self-healing processes; or aiming to relieve the pain through spinal cord afferent signaling or other mechanisms (42)(43)(44)(45). However, as many clinicians' experiences might indicate, these mysterious painful points recur a short while after treatment too often, if not in the same site, then in a different one.…”
Section: Dry Needlingmentioning
confidence: 99%